2011
DOI: 10.1021/jp110498x
|View full text |Cite
|
Sign up to set email alerts
|

Pristine and Hybrid Nickel Nanowires: Template-, Magnetic Field-, and Surfactant-Free Wet Chemical Synthesis and Raman Studies

Abstract: Nickel nanowires of high purity and various aspect ratios were synthesized by a wet chemical reduction method without the assistance of surfactants, templates, and external magnetic field. The observed unique optical absorption features of nickel nanowires are highly dependent on the nanowire dimensions. In order to tailor the physical and chemical properties of the nanowires, we have incorporated functionalities in the form of tellurium and zinc oxide coating on them by overgrowth processes using simple wet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 68 publications
1
43
0
Order By: Relevance
“…Taking the two strongest peaks of 1648 cm −1 and 1358 cm −1 into account, the relevant data required by equation (4) are listed in Table 2. The EF is calculated to be about 1.2 × 10 5 and 1.0 × 10 5 by using the peaks of 1648 cm −1 and 1358 cm −1 , respectively, and the average EF is 1.1 × 10 5 , which is 1–3 orders of magnitudes higher than that of the reported crystal Ni- or Pd-based NWs152627 and comparable to that of gold metamaterials and nanostar arrays528. It indicates that the nanostructures of MGNWA can exhibit strong SERS EF .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Taking the two strongest peaks of 1648 cm −1 and 1358 cm −1 into account, the relevant data required by equation (4) are listed in Table 2. The EF is calculated to be about 1.2 × 10 5 and 1.0 × 10 5 by using the peaks of 1648 cm −1 and 1358 cm −1 , respectively, and the average EF is 1.1 × 10 5 , which is 1–3 orders of magnitudes higher than that of the reported crystal Ni- or Pd-based NWs152627 and comparable to that of gold metamaterials and nanostar arrays528. It indicates that the nanostructures of MGNWA can exhibit strong SERS EF .…”
Section: Resultsmentioning
confidence: 86%
“…Just like in crystal MGNWAs, there also exist localized electromagnetic fields caused by the lightning rod effect around the NW tips in MGNWAs151626. In the a-type MGNWA, several NWs' tips attach each other, resulting the distances among them decreased significantly.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] A variety of research into metal-semiconductor composite nanostructures has found that the incorporation of 1D metal building blocks and semiconductors into integrated heterostructured photocatalysts allows for highly efficient separation and transfer of photoinduced charges. [1][2][3][4][5][6][7][8] A variety of research into metal-semiconductor composite nanostructures has found that the incorporation of 1D metal building blocks and semiconductors into integrated heterostructured photocatalysts allows for highly efficient separation and transfer of photoinduced charges.…”
Section: Introductionmentioning
confidence: 99%
“…Sample preparation: Nickel nanowires were synthesized by the wet chemical reduction method [9] with some modifications. In this synthesis, NiCl 2 Á 6H 2 O in ethylene glycol as a solvent was reduced by hydrazine hydrate to form nickel nanowires.…”
Section: Methodsmentioning
confidence: 99%